STRATEGIC APPROACHES TO REVERSE LOGISTICS: MANAGING RETURNS FOR SUSTAINABILITY - REDDY VUMMADI, JAYAPAL; CHAITANYA RAJA HAJARATH, KRISHNA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Reverse logistics, the process of managing the return of goods from the consumer back to the manufacturer, has gained increasing importance in today’s global supply chains. With the rise of e-commerce, consumer returns have become a significant challenge for companies, not only due to logistical complexities but also because of their environmental and financial implications. However, when managed strategically, reverse logistics can contribute to sustainability by reducing waste, promoting product reuse, and minimizing resource consumption. This research article examines the strategic approaches to reverse logistics, with a focus on managing returns for sustainability. It explores the environmental, economic, and operational benefits of an efficient reverse logistics system, outlines key strategies for improving returns management, and discusses the integration of circular economy principles into reverse logistics practices. Through case studies and industry examples, this paper highlights how organizations can optimize their reverse logistics processes to enhance both business performance and sustainability.